A elisão em dois portos : evidências para a comparação entre PB e PE - Alencastro, Ana Paula Mello (2013)
This study focuses on the process of elision of /a/, /e/ and /o/ at word boundaries in the speech of individuals from Porto Alegre-RS, Brazil and Porto, Portugal based on samples collected through personal experience interviews with 24 subjects from each of the places mentioned. The aim was not only to describe the process in both varieties but also to compare the results obtained with the same methodology. In order to do that, the analysis followed in light of Prosodic Phonology (NESPOR & VOGEL, 1986) and Variation Theory (LABOV, 1972) allowing the investigation of the action of prosodic aspects such as word boundaries, rhythm and speech rate, segmental aspects and social aspects like age and gender. Although the results of the statistical analysis run in Goldvarb have shown a higher frequency of elision in Porto compared to Porto Alegre- highlighting the epenthesis process that haven't been described as a systematic variable rule in Porto up to this moment - they indicated that the Phonetic Quality of the vowel in the Second Position, the Type of Sequence, Word Boundary and Word Stress Distance condition the elision process of vowels /a/, /e/ and /o/ in both varieties. Regarding the Phonetic Quality of the Second Position, we concluded that there is a dependency relation concerning the role of the stress of the target vowel and that, when unstressed, all vowels are favoring contexts for the application of elision. However, considering the variable Type of Sequence, the first position happened to be relevant. In this case, stressed function words as well as content words showed favoring behavior while clitics blocked the process. The statistical analysis revealed that the process is blocked in the context of intonational phrases. The discussion about the role of Prosodic Boundary was resumed taking the result of the acoustic analysis, which evidenced that the incidence of pause is the main cause of elision, regardless of the boundary in the context. Still considering the boundary, we also discussed the application of Prosodic Phonology (NESPOR & VOGEL, 1986) for classifying structures in spontaneous speech, once it was possible to find ruptures in all the boundaries tested. The result for the Word Stress Distance variable - the only one in which discrepancies between Porto Alegre and Porto were verified - led to the discussion on the rhythmic pattern of Brazilian Portuguese (BP) and European Portuguese (EP). The evidences showed that the first one tends to a syllabic pattern, and the second one tends to a stress pattern. Speech rate, which was analyzed according to acoustic measures, also suggested a syllabic rhythm in the variety from Porto Alegre for pointing out the subjects lower average of syllables per second and a lower production of elision. However, a stress pattern was attributed to the variety from Porto due to the higher frequency of elision and higher average rate of speech. Testing Speech Rate also made it possible to establish the distinction between age groups concerning the application of elision in Porto. With regards to the linguistic unity of Brazilian and European varieties, it could be argued that there is one system only, as the phonological process in question demonstrated the same conditioning for both samples, highlighting rhythm, which has already been asserted in literature as responsible for the main differences between those varieties.